Public administration and government responsibility in the digital era - Ayrat Ramilevich, Davletshin; Viktorovich Chepus, Aleksey; Viktorovna Mamitova, Natalia (Opción, 2019)
The article is devoted to the theoretical and methodological understanding of the government responsibility in the realities of the process of digitalization of state and society via the methods of analysis, synthesis, induction, deduction. As a result, the institution of responsibility in crimes and administrative offenses should be reflected in the Russian legislation in relation to senior officials of the executive power. In conclusion, public authorities should be fully integrated into the digital economy to fully perform their tasks.